Bipolar charge trapping for absorption enhancement in a graphene-based ultrathin dual-band terahertz biosensor. Issue 20 (15th September 2021) - Varshney, Gaurav; Giri, Pushpa
Abstract : Surface plasmons generated at the graphene dielectric interface can be altered by trapping the electric charge. Abstract : Surface plasmons generated at the graphene dielectric interface can be altered by trapping the electric charge. A technique is implemented for trapping the bipolar electric charge on the graphene surface and arranged in a desired way to enhance the performance of a monolayer graphene metamaterial based tunable, ultrathin, dual narrow band terahertz (THz) absorber. A monolayer graphene sheet placed on the dielectric substrate can provide dual-band resonance by utilizing the surface plasmons of the fundamental and third order mode index and an absorption of more than 99% and 50% can be obtained in the lower and upper band, respectively. The absorption is further enhanced to the level of perfect-absorption by utilizing the charge trapping mechanism on the graphene and generating bipolar charged nodes to create higher order surface plasmons. The multiple interference and reflection theory proves that the destructive interference in the dielectric layer is the cause of perfect absorption. The applied technique in the dual-band absorber configuration provides a tunable response which remains insensitive to the polarization and incident angle of the electromagnetic wave. The proposed perfect absorber can be utilized as a biosensor for refractive index sensing and the detection of glucose in water and the malaria virus in blood. It can provide an ultrahigh sensitivity of 14.88 THz RIU −1 with FOM as 53.09 RIU −1 with the variation in the chemical potential of graphene and 12.7 THz RIU −1 and FOM as 41.1 RIU −1 during glucose detection in water.